If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -7 = 4y + 5 Reorder the terms: -7 + 6y = 4y + 5 Reorder the terms: -7 + 6y = 5 + 4y Solving -7 + 6y = 5 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -7 + 6y + -4y = 5 + 4y + -4y Combine like terms: 6y + -4y = 2y -7 + 2y = 5 + 4y + -4y Combine like terms: 4y + -4y = 0 -7 + 2y = 5 + 0 -7 + 2y = 5 Add '7' to each side of the equation. -7 + 7 + 2y = 5 + 7 Combine like terms: -7 + 7 = 0 0 + 2y = 5 + 7 2y = 5 + 7 Combine like terms: 5 + 7 = 12 2y = 12 Divide each side by '2'. y = 6 Simplifying y = 6
| -4+11=14x-5-13x | | 63x+25x=300+25x | | 5-b=29 | | -6x+2x-9x= | | y+5y=3y | | 6x-10=2(2x+1) | | 23-13=5(x-1) | | 2x(2x)-224=0 | | -5(2y-10)-y=-4(y-5) | | 0.13y+0.05(y+5000)=1690 | | 6x-8x+2=x-3+5 | | -2(w+3)-w-5=-3(w+5)+4 | | x+24+4x=-26-4x-31 | | -5(w+2)-w-7=-6(w+4)+7 | | 3x-1=4x+1 | | -29p-6(5-6p)=3(p-4)-34 | | .5x(x)-242=0 | | 5z^2-7z=-3z-7 | | 4.9t^2+15t+1.9=0 | | (x+1.8)-(0.1x+7)=9 | | 1-5x-y=0fory | | -3(2-4n)=10 | | 0.34=logx | | (x+26)-(0.1x+8)=10 | | 7(5(x-1))+3=17 | | (x+2.7)-(0.7x+4)=12 | | -4x+6x-7=2(x-3)-4 | | 5+10x=4+10x | | 9x-5=2(4x+3)-1 | | -6(y+9)=-5y-5 | | 15z^4-13z^2+2=0 | | -7(z-3)=-6z-9 |